Determinants of Costa Rica's International Trade of Wastes and Its Relationship with the Circular Economy - Ugalde-Hernández, Oscar (2021)
As the circular economy has evolved into a new development model, international trade of wastes, scraps, and residues has grown with significant relevance in this new century. Costa Rica represented less than 0.1 percent of the total amount of world waste exports by the end of 2020, however; it can make a transition to a circular economy through this international trade trend. This article explores the determinants that propel Costa Rica to participate in this type of international trade. Through the application of a Poisson pseudo maximum-likelihood gravity model with a 2018 cross-sectional database of 47 countries, it is determined that Gross Domestic Product of importing countries, their population sizes, their services sectors’ size in terms of GDP, as well as their environmental performance, are all significant determinants. Trade of wastes should not be a form of exporting problems to other nations, but a means to take the local circular economy to a global scale.